The allure of starting afresh: the effects of mortality-related sadness on the effectiveness of fresh start appeals. (8th September 2020) - Septianto, Felix; Khan, Saira; Seo, Yuri; Shi, Linsong
Abstract : Purpose: This paper aims to examine how mortality-related sadness, as compared to other emotions such as fear, anger and happiness, can leverage the effectiveness of fresh start appeals. Design/methodology/approach: Drawing upon the consumption-based affect regulation principle, this paper investigates how sadness associated with mortality can elicit the appraisal of irretrievable loss, which subsequently increases the effectiveness of fresh start appeals. These predictions are tested across three experimental studies. Findings: Findings demonstrate that mortality-related sadness enhances donation allocations (Study 1), willingness to pay (Study 2) and favorable attitudes (Study 3) toward an advertisement promoted with a fresh start appeal. This effect is mediated by an appraisal of irretrievable loss (Studies 1–3). Moreover, the emotion's effect only emerges among consumers who believe that their emotional experiences are stable (vs malleable) (Study 3). Research limitations/implications: This paper investigates the effects of negative (vs positive emotions). It would thus be of interest to explore whether different discrete positive emotions may also enhance favorable evaluations of fresh start appeals. Practical implications: While fresh start appeals have been widely used by marketers and organizations, the extant literature in this area has yet to identify how marketers can leverage the effectiveness of such appeals. This paper highlights how a specific negative emotion can be beneficial to marketers in leveraging the effectiveness of fresh start appeals. Originality/value: The findings of this research suggest a novel potential strategy for the regulation of sadness. Specifically, consumers experiencing mortality-related sadness show favorable evaluations of fresh start appeals, indicating they are seeking to dissociate themselves from the past.